2005
DOI: 10.1093/humrep/dei298
|View full text |Cite
|
Sign up to set email alerts
|

Randomized single versus double embryo transfer: obstetric and paediatric outcome and a cost-effectiveness analysis

Abstract: The SET strategy is superior to the DET strategy, when number of deliveries with at least one live-born child, incremental cost-effectiveness ratio and maternal and paediatric complications are taken into consideration. The findings do not support continuing transfers of two embryos in this group of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
98
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(103 citation statements)
references
References 26 publications
2
98
0
3
Order By: Relevance
“…To ensure the applicability of this relative reduction to our modelled cohorts, we applied the same selection criteria for eSET as was used in the randomised controlled trials from which the multiplier was derived. 46 This approach yielded live birth rates following eSET that were congruent with those observed in other randomised trials. 6 A further weakness was that we were unable to assess relative cost-effectiveness of transferring blastocyst-stage embryos as opposed to cleavage-stage embryos.…”
Section: Strengths and Weaknessessupporting
confidence: 73%
“…To ensure the applicability of this relative reduction to our modelled cohorts, we applied the same selection criteria for eSET as was used in the randomised controlled trials from which the multiplier was derived. 46 This approach yielded live birth rates following eSET that were congruent with those observed in other randomised trials. 6 A further weakness was that we were unable to assess relative cost-effectiveness of transferring blastocyst-stage embryos as opposed to cleavage-stage embryos.…”
Section: Strengths and Weaknessessupporting
confidence: 73%
“…With respect to artificial reproductive techniques, the trend towards single embryo transfer might well lead to reduction of severe maternal morbidity because women with multiple pregnancies were at higher risk. 28 We found BMI to be an important risk factor for severe maternal morbidity. As the incidence of overweight and obesity is increasing rapidly in Western countries, we expect severe maternal morbidity to increase in the future.…”
Section: Discussionmentioning
confidence: 72%
“…early work by gerris et al (2004) showed, in a non-randomised study, that the transfer of a top-quality embryo was associated with significantly lower costs in women under 38 years during their first cycle. this observation was confirmed by Kjellberg et al (2006) with respect to the costs associated with complications of multiple pregnancy. many studies support the cost-effectiveness of eSet especially when cumulative rates with frozen embryo replacement cycles are taken into consideration with Scotland et al, (2011) providing a uK perspective.…”
Section: Cost Implications and Commissioning Considerationsmentioning
confidence: 55%